2017
DOI: 10.5005/jp-journals-10024-2036
|View full text |Cite
|
Sign up to set email alerts
|

Cariogenic Potential of the commonly Prescribed Pediatric Liquid Medicaments in Kingdom of Saudi Arabia: An in vitro Study

Abstract: Aim:The aim of this study was to assess the cariogenic potential of the commonly prescribed pediatric liquid medicaments (PLMs) for dental disease in Jazan region, Kingdom of Saudi Arabia. Materials and methods:Seven most commonly prescribed PLMs were selected by prior questioning the pediatric dentists as well as general dentists in Jazan region. The endogenous pH and sucrose concentrations of the liquid medicaments were assessed. The endogenous pH was assessed by Hanna pH meter instrument. The sucrose concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Many studies have been done in the US [4], Brazil [2], New Zealand [3], and Saudi Arabia [23] linking frequent use of sweetened LOM and the development of dental caries. Other authors studied the pH and concentration of sugars of pediatric liquid medicaments and suggested that these medications can pose as a threat to dental health [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done in the US [4], Brazil [2], New Zealand [3], and Saudi Arabia [23] linking frequent use of sweetened LOM and the development of dental caries. Other authors studied the pH and concentration of sugars of pediatric liquid medicaments and suggested that these medications can pose as a threat to dental health [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Most pediatric medicaments may contain certain acids in their liquids, which serve as a buffer to keep the solution’s chemical stability and tonicity under control and maintain physiological compatibility. They also enhance the flavor, which makes the drug more kid-friendly [ 14 ]. Since this is a pioneering study about the effect of orally supplemented lactoferrin on the enamel exterior of primary and permanent teeth, a pH meter was used to measure the pH of the lactoferrin suspension.…”
Section: Methodsmentioning
confidence: 99%